ANALISIS STRUKTUR ATAS GEDUNG 11 LANTAI DENGAN SISTEM RANGKA PEMIKUL MOMEN KHUSUS MENGGUNAKAN ETABS V22 : (Studi kasus : Pembangunan Gedung Onkologi RSUP Dr. Soeradji Tirtonegoro, Klaten, Jawa Tengah – Program Magang MBKM 2-2025) - Ramadhani, Ananda Ivan; Setioningsih, Retnowati; Zulaicha, Lilis (Jurnal Teknik Sipil dan Arsitektur, 2026)
The construction of the Oncology Service Center Building of RSUP Dr. Soeradji Tirtonegoro Klaten is motivated by the need to improve access, quality, and capacity of cancer healthcare services in Central Java through the provision of modern and integrated facilities as a comprehensive oncology referral center for diagnosis, therapy, and patient care. The building is designed as an 11-story structure employing a reinforced concrete moment-resisting frame system combined with shear walls as the primary lateral load–resisting elements, and utilizing a Special Moment Resisting Frame (SMRF) system to achieve high ductility and adequate seismic resistance, considering that Klaten is located in a seismically active region. This study aims to analyze the superstructure of the building using ETABS V22 in accordance with SNI 1726:2019 for seismic design, SNI 1727:2020 for minimum design loads, and SNI 2847:2019 for structural concrete requirements. The structural model includes columns, beams, and slabs, with gravity loads, wind loads, and seismic loads applied, where seismic actions are evaluated using the response spectrum method. The analysis results indicate that the internal forces, bending moments, shear forces, and axial forces in the structural elements remain within the design capacity limits. Furthermore, the evaluation of deflections and inter-story drift demonstrates compliance with the allowable limits, and the P–Delta effects are found to be within acceptable ranges. Overall, the structural system satisfies the requirements for strength, stiffness, global stability, and seismic performance in accordance with the applicable design standards.